3D Monitoring & its Significance in Tunneling: Special Emphasis on Tunnel T-74R of USBRL Project, India. Issue 1 (1st June 2022) - Ahmed, A; Mishra, S; Singh, A K; Azad, A
Abstract: Nowadays, Tunnels are the major transportation network throughout the world. The importance of tunnel and its associated system also increases as the demand of Tunnel construction increases day by day. It has its significant importance in water conveyance networks as well as communication networks. As it is spreading fast over the world, the assessments of deformations are becoming an important part of tunneling system. The paper deals with the 3D monitoring system for the safety perspective and to make proper judgement about the condition of tunnels related to the information obtained in the measuring equipments. It also enables to react under various rock setting with the precise and reliable monitoring results. As we observed in the T-74R tunnel, where deformation of the tunnel's support system is a natural occurrence, the T-74R's main support system was also affected. The groundmass is prone to deformation due to its poor state and proximity to the principal thrust. The finding of the T-74R tunnel utilising 3D monitoring devices is important. They have provided the information about actual ground behaviour conditions.